Sub-specialty in neurosurgery: Time has come for Nepal - Thapa, Amit (Nepal Journal of Neuroscience, 2021)
With over 90 practicing neurosurgeons in the country, should we be developing sub-specialty in neurosurgery? The number of trained manpower has risen steadily, since neurosurgery was first practiced in Nepal in 1961.1Though we are halfway to the milestone of achieving a ratio of 1 neurosurgeon for every 1 lac population, the situation here is much better than in other Sub-Saharan African and south east Asian countries.2 All the seven states have now neurosurgeons working in its hospitals, though most are still concentrated in the capitals and major towns.Recently for the last five years, despite of lack of training opportunities for sub-specialty in the country, we have seen young neurosurgeons getting trained in skull base, spine, minimally invasive or endoscopic neurosurgery, functional neurosurgery, pediatric neurosurgery and vascular neurosurgery from abroad. There is a variation in nature and period of training, ranging from observership of a few weeks to fellowship of over a year. The interest seems to be getting stronger as the facilities and complexities of cases are increasing. In such scenarios, rather than few individuals we need units or teams offering these sub-specialized services from key centers and start supervised systematic training for the interested.